Microtransplantation of human brain receptors into oocytes to tackle key questions in drug discovery. Issue 2 (February 2019) - Zwart, Ruud; Mazzo, Francesca; Sher, Emanuele
Highlights: Membranes prepared from post-mortem human brain tissues can be injected into frog oocytes. Human brain membranes fuse with the plasma membrane of the oocyte. Native human receptors appear on the surface of the oocyte. Their functional and pharmacological properties can be evaluated using a voltage clamp. Applications of this technique are discussed. Abstract : It is important in drug discovery to demonstrate that activity of novel drugs found by screening on recombinant receptors translates to activity on native human receptors in brain areas affected by disease. In this review, we summarise the development and use of the microtransplantation technique. Native receptors are reconstituted from human brain tissues into oocytes from the frog Xenopus laevis where they can be functionally assessed. Oocytes microtransplanted with hippocampal tissue from an epileptic patient were used to demonstrate that new antiepileptic agents act on receptors in diseased tissue. Furthermore, frozen post-mortem human tissues were used to show that drugs are active on receptors in brain areas associated with a disease; but not in areas associated with side effects.